Labor Market Participation among Young Adults: An Event History Analysis - JOHNSON, ROBERT J.; HERRING, CEDRIC (Youth & society, 1989)
A study investigated labor market participation among young adults using culture of poverty theories and opportunity-structure theories as guidelines. The timing of labor market entry and its consequences are discussed.